OPTIMUM SIZE OF RADIUS of CURVATURE FOR A TRAPEZOIDAL CHANNEL TO MINIMISE HYDRAULIC LOSS - Jain, Narinder Kumar; Goyal, M. R. (PREPARE@u® | IEI Conferences, 2021)
Optimum value of the radius of curvature to be provided to join the bed of a trapezoidal channel with side slopes has been worked out to minimize the head loss in the channel. It has been found to be equal to 0.4 R, where R is the mean hydraulic radius of the channel, for all values of side slopes. Provision of curves with a radius equal to the depth of the channel has been found to increase the head loss instead of decreasing it, thus defeating the very purpose for which it is provided.